Sterols and Stanols Preserved in Pond Sediments Track Seabird Biovectors in a High Arctic Environment - Cheng, Wenhan; Sun, Liguang; Kimpe, Linda E; Mallory, Mark L; Smol, John P; Gallant, Lauren R; Li, Jinping; Blais, Jules M (Environmental Science & Technology, 2016)
Seabirds are major vertebrates in the coastal ecosystems of the Canadian High Arctic, where they transport substantial amounts of marine-derived nutrients and pollutants from oceans to land by depositing guano and stomach oils to their nesting area, which often includes nearby freshwater ponds. Here we present novel indicators for evaluating the impact of seabirds on freshwater ecosystems. The ratio of cholesterol/(cholesterol + sitosterol) in pond sediments showed significant enrichment near a nesting colony of northern fulmars (Fulmarus glacialis) and was significantly correlated with ornithogenic enrichment of sediment as determined by sedimentary δ(15)N. The sterol ratio was also correlated with several bioaccumulative persistent organic pollutants (POPs), suggesting its usefulness in tracking biovector enrichment of contaminants. Human-derived epicoprostanol was also analyzed in the sediments, and its relationship with an abandoned, prehistoric camp was recorded, suggesting its potential as a tracer of prehistoric human activities in the Arctic. Sterols and stanols preserved in sediments appear to be useful geochemical tools that will inform our understanding of migratory species and the presence of prehistoric human populations in the Arctic, and possibly other animal populations.